2002
DOI: 10.1111/j.1151-2916.2002.tb00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of AlN Using CaO‐Al2O3 as a Sintering Additive: Chemistry and Microstructural Development

Abstract: The densification of aluminum nitride using Ca12Al14O33 as a sintering aid has been studied with emphasis on the effect of using coarse or fine powder, the amount of sintering aid, the sintering temperature, and embedding. Both crystalline and amorphous grain boundary phases were observed. Significant weight losses were observed for coarse‐grained samples, and if suitable embedding was not used. Porous and coarse‐grained ceramics with high contiguity and minor amounts of secondary phases were obtained by enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 14 publications
0
21
0
12
Order By: Relevance
“…Alguns estudos [16,67] utilizaram pó de grafita ou de negro de fumo como aditivo de sinterização, objetivando a formação in situ de uma atmosfera redutora dentro do corpo [67,76]. Em relação ao AlN com CaO, a evaporação de compostos ocorre durante a sinterização tanto em atmosfera redutora [48,64,77] como inerte (forno com elemento resistivo de tungstênio) [42]. Neste caso, observou-se maior evaporação de compostos à base de cálcio devido à elevada pressão de vapor do CaO [78].…”
Section: Sinterização Do Nitreto De Alumíniounclassified
See 1 more Smart Citation
“…Alguns estudos [16,67] utilizaram pó de grafita ou de negro de fumo como aditivo de sinterização, objetivando a formação in situ de uma atmosfera redutora dentro do corpo [67,76]. Em relação ao AlN com CaO, a evaporação de compostos ocorre durante a sinterização tanto em atmosfera redutora [48,64,77] como inerte (forno com elemento resistivo de tungstênio) [42]. Neste caso, observou-se maior evaporação de compostos à base de cálcio devido à elevada pressão de vapor do CaO [78].…”
Section: Sinterização Do Nitreto De Alumíniounclassified
“…1). Uma explicação para este fenômeno é que a densidade do AlN diminui em função do aumento do teor de CaO [42,38,65,77], o que indica a formação de poros, os quais limitam a condução de calor pela microestrutura. Em suma, a cerâmica de AlN tem extensa faixa de valores de l (50 a 270 W/mK) devido às diferenças nas características do pó de partida, aos diferentes aditivos de sinterização, aos diferentes parâmetros de sinterização e ao tratamento térmico pós-sinterização sob atmosfera redutora.…”
Section: Condutividade Térmica (L) Do Nitreto De Alumíniounclassified
“…The eutectic points in the CaF 2 -YF 3 system occur at 60 and 91 mol% CaF 2 at 1120º and 1106ºC, respectively (Seiranian et al, 1974). The studies on the thermodynamics taking place during sintering of AlN have been reported for AlN samples processed in organic media, therefore involving a residual amount of alumina at the surface of the AlN particles and the sintering additives (Buhr et al, 1991;Gross et al, 1998;Hagen et al, 2002;Hundere & Einarsrud, 1996;Medraj et al, 2005;Virkar et al, 1999). For samples processed in aqueous media, the presence of a protecting surface layer against hydrolysis makes the system more complex.…”
Section: Thermodynamic Studies On the Aln Sintering Powders Treated Wmentioning
confidence: 99%
“…No fluoride species could be detected after sintering in agreement with the thermodynamic predictions. Liquid phase sintering of AlN with CaF 2 at elevated temperatures (>1300ºC) results in a significant weight loss (Table 7) due to high vapour pressures generated by chemical reactions between AlN and the surface oxides as shown in equations (13) and (14) (Hagen et al, 2002).…”
Section: Thermodynamic Studies On the Aln Sintering Powders Treated Wmentioning
confidence: 99%
“…Hagen et al, [15] major portion of the synthesized C 12 A 7 with a CaO/Al 2 O 3 ratio of 0.94 cooled at 50 K/h changed into the metastable C 5 A 3 phase. The C 5 A 3 phase was also apparent for slag with a CaO/Al 2 O 3 ratio of 1.0 and 5 wt pct MgO that were isothermally cooled at 1543 K (1270°C).…”
Section: A Crystallization Of the Primary Phasementioning
confidence: 99%